FRI0172 The perioperative use of anti-tnf therapies in patients with rheumatoid arthritis undergoing elective orthopaedic surgery: a survey of current practice. (23rd January 2014) - Lee, M. A.; Perry, M.; Keenan, J.
Abstract : Background: An increasing number of patients with RA are now being managed with anti-TNF therapies. However, there appears to be some confusion amongst health care professionals working in both Rheumatology and Orthopaedics as to when these therapies should be discontinued prior to elective orthopaedic surgery. There is conflicting data in the current literature with regards to perioperative infection and anti-TNF use. The BSR recommendations sate that "if anti-TNF treatment is to be stopped prior to surgery, consideration should be given to stopping at a time 3 to 5 times the half-life for the relevant drug before surgery (infliximab 8-9.5 days, etanercept 100 hours, adalimumab 15-19 days)"[1 ]. There is some confusion as to whether the figures stated in the recommendations refer to the half-lives of the drugs themselves or the time the guidelines recommend stopping the drugs prior to surgery. Objectives: We conducted an e-mail survey of local practitioners to gain an understanding of current practice and whether that practice was in line with current national guidelines. Methods: An e-mail survey of 131 consultant rheumatologists, rheumatology specialty trainees and rheumatology specialist nurses working in South-West England and Wales was conducted. Health care professionals were asked when they routinely stop infliximab, etanercept and adalimumab prior to routine elective orthopaedic surgery. Results: 61 (47%) of health care professionals responded to the survey question, "How long prior to elective orthopaedic surgery do you routinely recommend stopping Infliximab, Etanercept and Adalimumab?" Conclusions: In South-West England and Wales, the period prior to elective orthopaedic surgery that infliximab and etanercept are stopped is in keeping with BSR recommendations. However, the period between when adalimumab is stopped and when elective orthopaedic surgery occurs appears to be shorter than BSR recommendations. One potential reason for this discrepancy is the perception that adalimumab's half-life may be shorter than 15-19 days as injections are given more frequently than one may expect when the pharmacological half-life is taken into account. It may also be that rheumatologist stop adalimumab in a way that they believe is manageable for the patient's arthritis. References: Ding T, Ledingham J, Luqmani R et al. BSR and BHPR rheumatoid arthritis guidelines on safety of anti-TNF therapies. Rheumatol 2010;49(11):2217-9 Disclosure of Interest: None Declared